Effects of grazing system and use of a pasture-phase implant on grazing and finishing performance of steers - Robert T. Brandt Jr.; C.T. Milton; Clenton E. Owensby (Kansas Agricultural Experiment Station Research Reports, 1995)
Results are presented from the first year of a 2-year study to evaluate the effects of grazing system (intensive-early stocking or IES vs season-long grazing or SLG) with or without a pasture-phase implant (Synovex-S®) on grazing and subsequent finishing performance. Compared to a SLG system, IES resulted in faster rate of gain on pasture and more beef produced per acre, although SLG resulted in greater total pasture gain per animal. Implanting improved rate of gain and increased beef per acre, particularly for IES steers. In the feedlot, IES steers gained weight faster and more efficiently than SLG steers. However, SLG steers had greater final live weights and carcass weights at a common backfat thickness . Pasture-phase implanting did not affect feedlot performance. For heavier SLG steers, final feedlot weights combined with a higher proportion of total gain being made on pasture offset their slower gains and higher cost of production. Implanting IES steers prior to grazing resulted in a numerical improvement in final feedlot weight and net return.
Keywords: Cattlemen' s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Grazing system; Finishing; Steers; Implant